ANALISIS PENGUASAAN TEKNOLOGI DALAM KESIAPAN KOTA KEDIRI MENUJU KOTA CERDAS (SMART CITY) - LIMANTARA, Arthur Daniel; SANTOSO, Elkana Lewi; Subagyo, Subagyo; SUBIYANTO, Bambang; SUDARMANTO, Hery Lilik; MUDJANARKO, Sri Wiwoho (Universitas Nusantara PGRI Kediri, 2020)
The demand for a city or environment that is comfortable, safe, healthy, easy, and prosperous is an indicator of a city that is competitive, and Kediri is no exception. Kediri City has positioned itself at level 3 smart city (smart city) and strives to reach level 5, to get to that level it is necessary to conduct an analysis of technical mastery of the three main players in smart city development in adopting technology in the six dimensions of smart city indicators. The methodology used is the Analytic Hierarchy Process approach to obtain the level of importance of the six smart city indicators by taking data based on interviews and questionnaires to the three main actors of smart city development, then analyzing using the techno-economic method to obtain the level of readiness in carrying out activities towards a smart city. The result is that the highest to the lowest level of readiness is Technoware of 0.957; Orgaware 0.874; Infoware 0.778; and Humanware 0.603. The conclusion is that there is a need for more intensive and targeted socialization and training to the public, business actors, and bureaucracy to better understand the implementation of smart city development so that it is more focused on achieving smart city.